Agustianto and Muhammad's Thoughts Regarding Financing Agreements and Their Relevance To Growth and Development Sharia Banking In Indonesia - Asmaul Husna; Ismail; Syahrul Wahyudi (Journal of Global Islamic Economic Studies, 2023)
This paper is a study that aims to investigate, identify, map, and analyze the thoughts of Agustianto and Muhammad related to hybrid contracts in Islamic banking and their relevance to the growth and development of Islamic banking in Indonesia. The research methodology used is a review of Agustianto's and Muhammad's thoughts in their books, articles, and videos, as well as verbal communication interviews with these figures. In addition, comparisons are also made to previous studies both on a local Indonesian scale and on an international scale. From this investigation, the results were found: first, the social, cultural, and educational backgrounds so clearly color the thinking patterns of Agustianto and Muhammad. Second, Agustianto and Muhammad are concerned with the development of sharia financing products, especially hybrid contracts. They both believe that hybrid contracts in the present and future are a necessity. Even Agustianto is currently successful in making his own manhaj regarding hybrid contracts, where he divides hybrid contracts into six types. Third, Agustianto consistently criticizes the lack of quality human resources in Islamic banking which can hinder the emergence of innovative financing products in Islamic banking. Meanwhile Muhammad criticized the implementation of many contracts in Islamic banking financing, it was clear that he was trying to put the contract in a fair implementation, for the bank as well as for the customer.